Comparative Study Of Clinical Outcome Of Laparoscopic Total Extraperitoneal Repair Vs Lichtenstein Repair In 50 Cases Of Inguinal Hernia (Indian Journal of Applied-Basic Medical Sciences, 2021)
INTRODUCTION Abdominal hernia includes groin hernia (70%), umbilical hernia (15%), epigastric hernia (7%) and incisional  hernia (9%). After Bassini’s published paper on the techniques of tissue repair, numerous modifications like use  of prosthetic material by Usher and open preperitoneal mesh repair introduced by Stoppa but these were associated  with significant postoperative pain and morbidity. The concept of Tension free open mesh repair was first  introduced by Lichtenstein. Totally extra peritoneal hernia repair (TEP) is a relatively new technique of repairing  inguinal hernias laparoscopically where the dissection and repair are carried out without violating the peritoneal  cavity laparoscopically. This study compares the results of laparoscopic hernioplasty by Total Extra-Peritoneal  (TEP) technique and Lichtenstein tension free repair hernioplasty technique by open method and determine if the  relative advantages achieved could be put in practice in large scale and also identify criteria which may help to  choose the patient to a particular type of repair to obtain encouraging results for that particular patient. METHODS AND MATERIALS: The present study was carried out with 50 patients admitted in the department of general surgery at our hospital  from period May 2018 to December 2019. Inclusion criteria: • Patient aged 18 years and above giving written valid consent. • Patients diagnosed as having unilateral incomplete inguinal hernia. • Patients medically fit to undergo the procedure. Exclusion criteria: • Single or multiple previous lower abdominal surgeries; • Complicated inguinal hernia, i.e., irreducible, obstructed, or strangulated; • Uncorrected coagulopathies; • Patients unfit for general anaesthesia RESULT In our prospective Comparative study of laparoscopic and open inguinal hernioplasty, we studied 50 patients with  unilateral direct inguinal hernia. Average operative time in open repair was 48 minutes and 70 minutes in  laparoscopic repair. In TEP, complications such as difficulty in dissection was seen in 3 patients (12%), accidental  opening of peritoneum in 2 patients (8%), and inadequate/inability to insufflate was seen in 1 patient (4%). On  postoperative day 7, 8 patients (32%) have mild pain and 3 patients (12%) have moderate pain after open hernia repair. And rest 14(56%) patients experienced no pain. After laparoscopic hernia repair 16 patients (64%) have  no pain and 7 patients (28%) have mild pain and 2 patients (8%) had moderate pain. Duration of hospital stay in  open (3.5 days) is more compared to laparoscopic repair (2.5 days). Return to normal routine activities in open  repair (15.3 days) is delayed than laparoscopic repair (12.92 days). CONCLUSION Here, we have done prospective comparative study of clinical outcome of laparoscopic TEP Vs Lichtenstein open  inguinal repair in 50 cases of inguinal hernia. We have reached to following conclusion in our study. • Incidence of wound infection and scrotal edema are more in open repair then TEP. • TEP is less painful in the early postoperative period leading to earlier ambulation than open  repair. • TEP results in significantly earlier return to work and better cosmetic results. • TEP results in decreased hospital stay and faster recovery than open repair. • Average operative repair in TEP is more (70 mins) compared to open repair (48mins) • Issue of steep learning curve for laparoscopic surgery should be addressed with better  supervision and standardization of training in laparoscopy
Keywords: Inguinal Hernia; Laparoscopy; Extraperitonial Repair